Study Some Mechanical Properties of Mortar with Sawdust as a Partially Replacement of Sand - Muhsan Hasan Bdeir, Layla (Anbar Journal of Engineering Sciences, 2012)
Some mechanical properties of mortar (compressive strength and hardness) with sawdust replacement of sand were investigated. Cubes of 50 mm × 50 mm were prepared, the compressive strength tests were done for a replacement levels ranging (5, 10, 15, 25, 50, 75) % by volume a reference mix were also prepared for comparison this test was done after 7, 14, and 28 days while hardness test were done after 28 day for a replacement levels (0, 5, 10, 15, 25) % by volume. Result showed that the compressive strength of the specimen were decreased with higher sawdust content, hardness values were decreased slightly in the replacement levels 0, 5, 10 % while the values began to decrease noticeably in the replacement levels 15 and 25 % the hardness values were (59, 57.5, 56, 47.77 , 45.2) N/mm2 respectively A cost analysis was done, this analysis was based on a unit of mortar (1.0 m3) made from conventional materials and a modified concrete made by substituting materials with sand using sawdust